PELAYANAN UNIT PELAKSANA TEKNIS TEKNOLOGI INFORMASI DAN KOMUNIKASI UNIVERSITAS RIAU DALAM PENGISIAN KRS MAHASISWA DI FISIP TAHUN TAHUN 2017 - Rahmat Ismail; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
The use of e-Government for the government is to create effective and efficient services. It is undeniable that every institution or higher education institution will carry out the provision of services as one of the main tasks for the smooth running of existing activities such as academics, student affairs, security and others. As for the formulation of the problem in this research, namely: First, How is the Service of the Technical Implementation Unit of Information and Communication Technology at the University of Riau in Filling the Student KRS at FISIP in 2017. Second, how are the obstacles to the Technical Implementation Unit of Information and Communication Technology at the University of Riau in Filling the KRS Students at FISIP in 2017.The objectives of writing this thesis are: First, to find out the services of the Technical Implementation Unit of Information and Communication Technology at the University of Riau in Filling Out Student KRS at FISIP in 2017. Second, to describe the constraints of the Information and Communication Technology Technical Implementation Unit of the University of Riau in Filling Out Student KRS at FISIP 2017. This research is a qualitative research. This research was conducted at UPT-TIK University of Riau. The techniques used to collect data in this research are (1) Interview, and (2) Document tracing.The conclusion of this study shows that the Service of the Technical Implementation Unit of Information and Communication Technology at the University of Riau in Filling the Student KRS at FISIP in 2017 uses six 6 aspects of which it is still not running effectively, the author gives suggestions that it is better to provide comfort in providing services, because UPT-TIK is the front line in supporting the success of an educational institution, apart from that, it is expected to pay more attention to the field of advice and infrastructure such as the provision of limited seats and the comfort of queuing rooms.  Keywords: UPT-TIK, in providing services.